Propuesta para aportar al incremento de los niveles de competitividad de la logística del transporte potencializando la navegabilidad del Río Magdalena (2018)
The Magdalena River is the largest tributary that Colombia has, with the largest extension, which crosses from the center to the north of the country, ending in the Atlantic Ocean. For this reason, activities such as fishing, tourism and other economic activities allow riparian municipalities benefit and find different employment modes. Currently the river is drifting, which is waiting for which company will develop the recoverability of it, as it has precarious conditions, such as sedimentation, poor transit of goods and passengers, infrastructure of the river ports is not in good condition except the port of Barrancabermeja, in the case of institutionality only Cormagdalena is responsible for monitoring and controlling the tributary.